2006
DOI: 10.1002/cbm.54
|View full text |Cite
|
Sign up to set email alerts
|

Social‐cognitive determinants of help‐seeking for mental health problems among prison inmates

Abstract: Social-cognitive factors predicted intentions to seek help among New Zealand prisoners but prison-specific issues, such as relative reluctance to seek help when suicidal and reluctance to seek help from prison psychologists, were also identified. Implications for practice Prisoners'; access to services could be improved, for example, through directly working on attitudinal barriers. Strategies to ensure access to specialized forensic mental health in-reach services could also be an alternative or additional ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 34 publications
5
56
1
Order By: Relevance
“…Skogstad, Deane, and Spicer (2006) first investigated psychological help-seeking intentions among a sample of 527 male New Zealand prison inmates. Using multiple regression analyses, the TPB model was found to explain 44% of variance in intentions, with all three of the direct determinants significantly predicting intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Skogstad, Deane, and Spicer (2006) first investigated psychological help-seeking intentions among a sample of 527 male New Zealand prison inmates. Using multiple regression analyses, the TPB model was found to explain 44% of variance in intentions, with all three of the direct determinants significantly predicting intentions.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is inconsistent with other studies on helpseeking attitudes with different populations. Skogstad et al (2006) found that attitude was the strongest predictor of the prisoners' help-seeking intentions. The participants' overall average scores on the Attitudes towards Seeking Mental Health Services (IASMHS) suggested positive general attitudes toward seeking mental health services; however, attitude was a weak predictor of the students' intentions to seek mental health services.…”
Section: Discussionmentioning
confidence: 93%
“…Ajzen's (1991) Theory of Planned Behavior, which is an extension of the Theory of Reasoned Action (Fishbein & Ajzen, 1975), suggests that a person's attitudes toward a given behavior, subjective norms in relation to the behavior and perceived control over the behavior are typically good predictors of intentions to perform the behavior. Ajzen's (1991) Theory of Planned Behavior has been used in a wide variety of research to predict and understand a range of behaviors, and help-seeking intentions (Skogstad, Deane, & Spicer, 2006;Mo & Mak, 2010;Westerhof, Maessen, de Bruijin, & Smets, 2008). To better understand this theory's utility for predicting mental health help-seeking intentions among international and African-American college students, it is critical to explore the influence of the components of this model on mental health utilization among these students.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…In a much larger sample Skogstad et al (2006) also assessed the intentions to seek help for personal-emotional problems. The general attitude towards seeking professional psychological help influenced the intentions to seek help, as did interpersonal factors like social pressure.…”
Section: Need For Carementioning
confidence: 99%